Analisis Transformasi Struktural Perekonomian di Provinsi Sulawesi Selatan Tahun 2010-2018 - St. Reski Amalia; Tuti Supatminingsi; Muhammad Ihsan Said; Muhammad Dinar; Muhammad Hasan (Indonesian Journal of Social and Educational Studies, 2020)
. This research aims to find out the base sectors and economic structure transformation in Province Sulawesi Selatan, so that they can be used as input for government policies. This study uses LQ (location Quotien) and Shift-share analysis tools.  This study uses secondary data, namely South Gross Domestic Regional Product Sulawesi Selatan 2010-2018. The results showed that there were nine base sectors, namely agriculture, forestry, and fisheries, water procurement, wholesale and retail trade; repair of motor vehicles and mototrcycle, construction, information and communication, real estate, government administration, defense and mandatory social security, education services and health services and social activities. In addition, it was found that there was a shift in the economy from the primary sector to the tertiary sector with a relatively small value, so South Sulawesi was included in the area that experienced progressive development.